Initial establishment of a multiplex real-time PCR assay for simultaneous detection of common colistin and carbapenemase genes - Thuy, Le Thi; Minh, Do Quang; Hang, Le Thi Thu; Quyen, Dong Van; Bañuls, Anne-Laure; Huy, Nguyen Quang (Vietnam Journal of Science and Technology, 2024)
Carbapenem and colistin are often used as last-resort treatment for Gram-negative multi-drug resistant (MDR) bacteria. Nevertheless, co-resistance of these drugs is threatening the global healthcare system. Rapid and accurate detection of carbapenem and colistin resistant bacteria is critical for adequate antibiotic therapy and infection control, particularly in the context of an outbreak. The presence of blaNDM, blaKPC, blaIMP-1 and blaOXA-48 is responsible for greater than 95% phenotypic resistance in carbapenem-resistant Enterobacteriaceae, while mcr-1 is the most prevalent and well disseminated of all mcr genes in colistin-resistant strains. In this study, we aim to develop a multiplex real time-PCR assay for simultaneous detection of the five genes blaNDM, blaKPC, blaIMP-1, blaOXA-48 and mcr-1. The melting curve-based multiplex real time PCR assay was established with the dissociation temperature range extended from 76°C to 87°C. The whole process is completed within one hour and half, allowing rapid screening of the five genes in cultured bacteria samples with a limit of detection of 10 CFU/ml. The proposed multiplex real-time PCR assay is a robust, reliable and rapid method for the detection of bacterial strains carrying blaOXA-48, blaIMP, blaNDM, blaKPC and mcr-1 gene individually or in cocktail of genes. This assay will be a valuable tool for surveillance and monitoring of MDR bacteria additionally resistant to either carbapenem or colistin or both drugs.